Utility of Multilocus Variable-Number Tandem-Repeat Analysis as a Molecular Tool for Phylogenetic Analysis of Shigella sonnei - Chiou, C.S.; Watanabe, H.; Wang, Y.W.; Wang, W.L.; Terajima, J.; Thong, Kwai Lin; Dac, C.P.; Tung, S.K. (2009)
A panel of 916 isolates, including 703 closely related IST1 isolates, were characterized by inter-IS1 spacer typing (IST), pulsed-field gel electrophoresis (PFGE), and multilocus variable-number tandem-repeat (VNTR) analysis (MLVA) to evaluate the utility of MLVA as a molecular tool for the phylogenetic analysis of Shigella sonnei. The global phylogenetic patterns determined by IST, PFGE, and MLVA were concordant. MLVA was carried out using 26 VNTR loci with a range of degrees of variability. MLVA data for the 703 IST1 isolates revealed that diversification among the closely related isolates was attributed mainly to four highly variable loci. The phylogenetic pattern for the closely related isolates determined using MLVA profiles of 8 highly variable loci was in agreement with that determined using the 26-locus profiles. A clustering analysis using the profiles of 18 loci with limited variability established clear phylogenetic relationships among IST clonal groups. Accordingly, MLVA is a useful tool for the phylogenetic analysis of S. sonnei. Combined VNTR loci with higher variability are useful markers for resolving closely related isolates, whereas combined loci with lower variability are suitable for establishing clear phylogenetic relationships between strains or clones that have evolved over a longer timescale.